Presence of Phlebotomus perniciosus Atypical Form in Algeria - Kamel Eddine Benallal; Razika Benikhlef; Rafik Garni; Brahim Gassen; Jean-Pierre Dedet; Zoubir Harrat (Journal of Arthropod-Borne Diseases, 2017)
Background: Phlebotomus perniciosus and Phlebotomus longicuspis are two phlebotomine sand fly species morphologically similar and differing in males only by the shape of the copulatory valves which are bifurcated in P. perniciosus, tip long and tapered in P. longicuspis. Methods: A count of the median coxite setae was carried out on 208 specimens from the collections of Dedet and of Parrot, identified previously as P. longicuspis and on 38 P. perniciosus male sand flies captured during the year 2012–2013, in order to seek the presence of atypical P. perniciosus form. Results: The analysis revealed the presence of 33/246 (13%) atypical P. perniciosus previously confused with P. longicuspis species and whose distribution is mainly located in the semi-arid and arid bioclimatic regions. Conclusion: This study proved for the first time the presence of atypical form of P. perniciosus in Algeria.